MULTIVARIATE ANALYSIS FOR THE ASSESSMENT OF HERBACEOUS ROADSIDES VEGETATION OF WAH CANTONMENT - H. Bashir; S. S. Ahmad; A. Jabeen; S. Erum (Journal of Animal and Plant Sciences, 2016)
The present research was conducted along the roadside of Wah Cantonment to determine the associations and relationships between the plant communities and soil, grouping and quantification of plant communities using multivariate ordination techniques. Braun-Blanquet technique was applied for herbaceous data collection and quadrats of 1 1 square meter were laid. The whole floristic data were collected from 50 different sites through random sampling and cover values for plants were predicted through visual estimation.A whole of 36 species belonging to 18 different families were indentified. The ordination techniques of TWINSPAN (Two Way Indicator Species Analysis) and DCA (Detrended Correspondence Analysis) were carried out to classify the data. TWINSPANdivided the whole data into four groups with two major groups having communities of Vicia-Verbena, Convolvulus-Parthenium, Cynodon-Rumex and Euphorbia-Lepidium while minor groups had communities of Cannabis-Dicliptera and Coronopus-Sisymbrium. DCAwas used to classify the data and it identified the cluster of species in ordinate space, divided the data in four groups, and verified the results obtained from TWINSPAN. Cynodondactylon and Cannabis sativa were emerged as the most dominant and second dominant species after DCA.The present study will provide the baseline information about the roadside vegetation of Wah Cantonment and will be helpful for preserving and better management of the native flora.
Keywords: Cannabissativa; Cynodondactylon; DCA; TWINSPAN; Wah Cantonment